2016
DOI: 10.3835/plantgenome2016.02.0021
|View full text |Cite
|
Sign up to set email alerts
|

Improving Genetic Gain with Genomic Selection in Autotetraploid Potato

Abstract: Potato (Solanum tuberosum L.) breeders consider a large number of traits during cultivar development and progress in conventional breeding can be slow. There is accumulating evidence that some of these traits, such as yield, are affected by a large number of genes with small individual effects. Recently, significant efforts have been applied to the development of genomic resources to improve potato breeding, culminating in a draft genome sequence and the identification of a large number of single nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(170 citation statements)
references
References 146 publications
5
162
2
1
Order By: Relevance
“…In diploid species, this is equivalent to the additive model (parameterized as {0,1,2} and assuming that the SNP effect is proportional to the dosage of the minor allele). In autotetraploids, this parameterization might be interpreted as a partial dominance model suggesting that any order of interaction between alleles reduces the genotypic value (Gallais, 2003;Slater et al, 2016). Our results showed that "diploidized models" were valid for scar diameter, fruit size, and soluble solids traits under a q-value threshold of 0.05.…”
Section: Snp-trait Associations In Autotetraploid Blueberriesmentioning
confidence: 65%
See 1 more Smart Citation
“…In diploid species, this is equivalent to the additive model (parameterized as {0,1,2} and assuming that the SNP effect is proportional to the dosage of the minor allele). In autotetraploids, this parameterization might be interpreted as a partial dominance model suggesting that any order of interaction between alleles reduces the genotypic value (Gallais, 2003;Slater et al, 2016). Our results showed that "diploidized models" were valid for scar diameter, fruit size, and soluble solids traits under a q-value threshold of 0.05.…”
Section: Snp-trait Associations In Autotetraploid Blueberriesmentioning
confidence: 65%
“…This parameterization disregards the allele dosage and all heterozygotes are grouped into the same genotypic class, which is at the midpoint between the two homozygotes (Rosyara et al, 2016;Slater et al, 2016). In diploid species, this is equivalent to the additive model (parameterized as {0,1,2} and assuming that the SNP effect is proportional to the dosage of the minor allele).…”
Section: Snp-trait Associations In Autotetraploid Blueberriesmentioning
confidence: 99%
“…This study has revealed that interpretation of GWAS in genetic architecture and population structure is a useful tool to enhance rice breeding through genomic selection (Spindel et al, 2015). In potato Slater et al (2016) reported that for four key traits with varying heritability, genomic selection is more accurate using genome-wide SNPs and can improve genetic gain (Slater et al, 2016).…”
Section: Genomic Selectionmentioning
confidence: 99%
“…As well as that, knowledge of genome-wide inheritance could help facilitate so-called "genomic selection", which has been advocated for polyploid breeding (e.g. (Slater et al, 2016)) but has yet to be shown to produce substantial gains in practice. Genomic selection theory as currently implemented assumes that all markers are potentially in linkage disequilibrium with genes that affect quantitative traits of interest (Meuwissen et al, 2001;Meuwissen et al, 2016), and therefore very large marker datasets are often used.…”
Section: Opening the Polysomic "Black Box"mentioning
confidence: 99%
“…It has been suggested that despite 150 years of breeding for increased yield, phenotypic selection methods have done nothing to raise average potato yields in that time (Jansky, 2009;Slater et al, 2016), in contrast to other major diploid crops like maize or rice. On the other hand, some authors remain convinced about the merit of polyploids and their potential to deliver higher yields through heterosis (Renny-Byfield and Wendel, 2014).…”
Section: Where Next For Polysomic Polyploid Breeding?mentioning
confidence: 99%